Demystifying the rubric: a five-step pedagogy to improve student understanding and utilisation of marking criteria. Issue 1 (2nd January 2017) - Jones, Lorraine; Allen, Bill; Dunn, Peter; Brooker, Lesley
ABSTRACT: Marking-criteria rubrics are commonly used to judge the quality of student work, but few students receive instruction to effectively use and apply rubrics. This study investigates an intervention designed to encourage effective utilisation of rubrics. The study, completed over two years (2011: n = 189 respondents; 2012: n = 464 respondents) in a large first-year course, explored how five instructional activities, used formatively and sequentially impacted student learning. This intervention comprised: (1) deconstruction of the rubric and standardising the marking method; (2) examples and exemplars; (3) peer review; (4) self-review; and (5) a reflective diary. Results showed an increase in student confidence with marking criteria and assessment (89% in 2011) and a statistically significant improvement in marks. Most students (77% in 2011 and 90% in 2012) rated each intervention as useful. Student feedback indicated that substantial changes occurred between initial drafts and final submission, which resulted in improvements in student performance scores.